The Banyumas Regency Islamic Religious Extension Strategy in Strengthening Religious Moderation - Uus Uswatusolihah; Dedy Riyadin Saputro (Universitas Medan Area, 2023)
This article aims to examine the communication strategies of Islamic Religious Counselors in Banyumas Regency in strengthening religious moderation. The problem focuses on the strategy of Islamic Religious Counselors in promoting religious moderation in the post-Covid 19 pandemic era. This research is qualitative research with a descriptive approach. The theories used in this research are Harold Laswell's communication theory, Uses and Gratification theory, and Campbell's theory of religious encounters and new media. Data collection was carried out through observation, interviews, and document analysis. The research informants, consisting of 30 Islamic Religious Counselors in the Banyumas Regency, were selected through purposive sampling based on the research objectives. This study concludes that Islamic Religious Counselors in Banyumas Regency, first, employ a strategy involving planning, understanding the characteristics of the target audience for da'wah (religious outreach), determining the material to be conveyed, selecting the delivery method, and choosing the communication media. Second, they carry out strategic planning by enhancing their knowledge of religious moderation through participation in workshops, training sessions, and independent study. They also conduct religious moderation outreach to congregations, both in face-to-face interactions and through media platforms such as radio, Facebook, WhatsApp, and YouTube. Furthermore, they practice religious moderation in various contexts, including interactions with Muslims, adherents of local culture, and followers of other religions. This research is valuable for the development of studies on strategies for promoting religious moderation at the grassroots level.